STUDY OF PROBLEM-SOLVING ABILITY ON ADDITION, SUBTRACTION, MULTIPLICATION, AND FRACTION USING POLYA’S PROBLEM-SOLVING PROCESS WITH GRAPHIC ORGANIZER INSTRUCTIONAL MODEL FOR THIRD GRADE STUDENTS - Chinprasert, Thanaporn; Dokchan, Rakporn (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The purposes of this research were 1) study the ability and learning achievement of the third-grade students to solve problems on addition, subtraction, multiplication, and fraction after using Polya’s problem-solving process with Graphic Organizer Instructional Model. The sample group of this research was 30 of third-grade students in the first semester of 2022 academic year from Watsawangmanus School, Lang Suan District, Chumphon. They were selected by using Cluster Random Sampling. The instruments of this research were (1) the lesson plans on problem-solving questions of addition, subtraction, multiplication, and fraction of the third-grade students using Polya’s problem-solving process with Graphic Organizer Instructional Model, with an appropriateness average of 4.49 – 4.84, (2) a test of problem-solving ability, with the Index of Consistency (IOC) between 0.67-1.00, difficulty (p) between 0.47-0.63, discriminating power (r) between 0.27-0.63 and the reliability of the whole version equal to 0.74. and (3) learning achievement tests, with the Index of Consistency (IOC) between 0.67-1.00, difficulty (p) between 0.470-0.60, discriminating power (r) between 0.20-0.53 and the reliability of the whole version equal to 0.87. Statistics used in data analysis were percentage, mean, standard deviation, t-test for one sample and independent t-test for dependent samples. The research findings were as follows. The ability and learning achievement to solve problems on addition, subtraction, multiplication, and fraction of the third-grade students after being taught using Polya’s problem-solving process with Graphic Organizer Instructional Model were 75.36 and 80.00 respectively, was higher than the criterion of 70 percent with a statistically significant of the 0.05 level.